(untitled) (Latakia University Journal -Biological Sciences Series, 2020)
The result of this study revealed clear variation in the Climatological condition between the main pistachio cultivation regions in Syria ,this variation in Climatological conditions led to variation in the yield of pistachio ( 12.46, 12.28,12.35) kg/tree with increase during the period (1986 -2011) was( 0.40 , 0.13 , 0.1 )kg/tree/year for Aleppo ,Idleb and Hama, respectively. Thermal accumulation for the period from flowering to maturity showed clear increase (192.37, 334.25,173.48), with decreased the number of chilling hours during the winter period by (- 68.70, -120.83, - 53.13) for Idleb, Hama, Aleppo, respectively. The values of simple correlation coefficient (-0.45 ...0.52) showed a strong positive and negative effect of some climatic elements during different periods of the year. Finally, the multiple regression equations linked between pistachio productivity and the most important effective climatic elements during different phenological stages in each of the three studied areas.